Population genetic structure and mixed stock analysis of the green sea turtle, Chelonia mydas, reveal reproductive isolation in French Polynesia - Dolfo, Violaine; Gaspar, Cécile; Bourjea, Jérôme; Tatarata, Miri; Planes, Serge; Boissin, Emilie (Frontiers in Marine Science, 2023)
The green turtle, Chelonia mydas, is a migratory marine species with a circumglobal distribution in tropical and temperate waters. Its natal homing behavior leads to a complex genetic structure with genetically differentiated populations that breed separately and mix within the same foraging grounds. Delineating the boundaries of these populations and their connectivity to feeding grounds is important for the management of this species, classified as endangered on the IUCN red list. Here, we examined the genetic structure and the origin of the green turtle in French Polynesia with 239 samples collected during nesting or hatchling events and 204 samples collected outside of nesting events, across 21 islands. Amplification of the 770pb mtDNA control region fragment, the standard base used to characterize haplotype diversity in this species, revealed 23 haplotypes including three novel ones, belonging to 6 different lineages. Haplotype diversity in the rookeries was 0.615, and nucleotide diversity was 0.019, values similar to those in the North West Pacific and Western Indian Oceans, two regions recognized as genetic diversity hotspots for C. mydas. The genetic structure between the Leeward and Windward Islands of the Society archipelago was found to be significant with pairwise Fst index and φst distance. Island groups (Windward Islands, Leeward Islands, Tuamotu) were genetically different from all other identified Pacific management units, with a weak differentiation between American Samoa and Leeward Islands. A mixed-stock analysis for the French Polynesian mixture revealed an exclusive contribution from the French Polynesian rookeries, with negligible input from the other Pacific populations. This study provides the first assessment of the genetic structure of green turtle populations within French Polynesia and fills an essential data gap regarding the genetic diversity of the species and its connectivity to other feeding grounds in the Pacific Ocean. The French Polynesian populations appear to be important contributors to the overall genetic diversity of the species, isolated from other Pacific populations, thus making them essential within the Pacific region. These results have important implications for the conservation of the species at both local and regional scales.